1992
DOI: 10.1161/01.str.23.8.1138
|View full text |Cite
|
Sign up to set email alerts
|

Time course of cerebral blood flow and histological outcome after focal cerebral ischemia in rats.

Abstract: Background and Purpose:The relation between time-dependent changes in cerebral blood flow and the appearance of infarction after focal cerebral ischemia is still a matter for debate. The aim of this study was to measure perfusion after simultaneous occlusions of the left middle cerebral artery and ipsilateral common carotid artery in rats and correlate it with the timing and distribution of histological changes.Methods: We studied histological and cerebral blood flow changes 5 minutes and 4, 24, and 48 hours a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 17 publications
(17 reference statements)
2
20
1
Order By: Relevance
“…Histopathological studies in focal ischemic rats demonstrated growth of infarction from 4 to 24 h postocclusion, although blood flow was stable in most ischemic structures (Hakim et al, 1992). This is in line with our finding of a progressive deterio ration of the EEG power spectrum and suggests that penumbral tissue suffers an increasing mis match between metabolic demands and substrate supply.…”
Section: Discussionsupporting
confidence: 90%
“…Histopathological studies in focal ischemic rats demonstrated growth of infarction from 4 to 24 h postocclusion, although blood flow was stable in most ischemic structures (Hakim et al, 1992). This is in line with our finding of a progressive deterio ration of the EEG power spectrum and suggests that penumbral tissue suffers an increasing mis match between metabolic demands and substrate supply.…”
Section: Discussionsupporting
confidence: 90%
“…1 Both primary and secondary injury do not develop uniformly in the brain; the severity and progression of damage show considerable regional differences. This region-specific response has been reported predominantly in transient global ischemia models [2][3][4] but has also been recognized in experimental focal ischemia 5,6 and after cardiorespiratory arrests in humans. 7 Certain brain areas, such as the hippocampal CA1 region, are extremely susceptible to a reduction in the supply of oxygen and glucose and inevitably become damaged.…”
mentioning
confidence: 67%
“…We measured CBF in cortical and subcortical areas of interest 17 in awake animals treated with 0.3 mg/kg per day candesartan, 0.1 mg/kg per day nicardipine, or vehicle for 28 days, 3 hours after MCA occlusion, by a modified quantitative autoradiographic technique using 4-iodo-[N-methyl- 14 C]antipyrine. 18 We quantified local tissue concentrations of 14 C by autoradiography.…”
Section: Measurement Of Cbfmentioning
confidence: 99%